Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1046/j.1365-2036.2003.01821.x
|View full text |Cite
|
Sign up to set email alerts
|

Rabeprazole 10 mg twice daily is superior to 20 mg once daily for night‐time gastric acid suppression

Abstract: Rabeprazole 10 mg twice daily, not 20 mg once daily, should be administered to achieve more potent and long-lasting acid suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 37 publications
2
44
2
Order By: Relevance
“…has been proposed. [5][6][7][8][9][10][11] While b.d. administration has generally been shown to better control night-time acid secretion, a significant percentage of subjects still experience NAB.…”
Section: Introductionmentioning
confidence: 99%
“…has been proposed. [5][6][7][8][9][10][11] While b.d. administration has generally been shown to better control night-time acid secretion, a significant percentage of subjects still experience NAB.…”
Section: Introductionmentioning
confidence: 99%
“…Several trials of PPIs have investigated the efficacy of this tactic [35,36,37,38]. A study of healthy volunteers who were each given 3 regimens of omeprazole (40 mg before breakfast, 40 mg before dinner, or 20 mg before breakfast and dinner) showed that dosing omeprazole at dinner or split dosing twice a day is significantly more efficacious in controlling nighttime gastric acidity than dosing before breakfast [35].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies of once-daily vs. twice-daily rabeprazole have also demonstrated the superiority of the twice-daily regimen in controlling nighttime acid breakthrough [37, 38]. A recent study in healthy subjects comparing the efficacy of rabeprazole 20 mg dosed in the morning vs. rabeprazole 10 mg dosed in the morning and the evening showed that the twice-daily regimen was associated with more effective inhibition of nighttime acid secretion [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, investigators have also attempted to eliminate NAB by targeting the night time histamine surge, with administration of histamine H2 receptor antagonists (H2RA) ( Table). 2,[4][5][6][7][8][9][10][11][12] What is the treatment effect of PPIs, which are known to have a longer plasma half-life on NAB? In this issue of the Journal of Neurogastroenterology and Motility, Karyampudi et al 13 evaluated esophageal acidification during NAB with ilaprazole, versus omeprazole in patients with uncomplicated GERD, in a prospective manner.…”
mentioning
confidence: 99%